Post-treatment serum triglyceride: An effective biomarker for body fat mass and overall survival in esophageal squamous cell cancer patients treated with chemoradiotherapy - Lyu, Jiahua; Yang, Ningjing; Guan, Wang; Xiao, Ling; Nie, Xinyu; Liang, Long; Bai, Hansong; Li, Churong; Kuang, Hao; Wang, Xiao; Li, Tao (Frontiers in Nutrition, 2022)
Objectives: Although lipids have been assessed for their possible roles in cancer survival prediction, studies on the association between serum triglyceride (TG) levels and the prognosis of esophageal squamous cell carcinoma (ESCC) patients are limited. This study aimed to evaluate whether serum TG is associated with outcomes in patients with ESCC and investigate any interaction between serum TG and clinical parameters, especially body fat mass. Methods: We conducted a prospective case study on patients diagnosed with ESCC between March 2012 and November 2018. We measured patients' serum TG levels before and after treatment. The association between serum TG and overall survival (OS) was evaluated using hazard ratios. We sought to determine a threshold point using optimal stratification. Survival analysis was performed using Kaplan–Meier curves and a Cox proportional hazards model. Results: Of the 257 participants diagnosed with ESCC, 200 (77.8%) were men. Median follow-up time was 22.4 months (range 3.3- 92.4 months). Using univariate Cox proportional hazard analysis and subsequent multivariate analysis, post-TG levels, Karnofsky performance scores, T stages, and chemotherapy cycles were shown to be independent prognostic factors for OS (p < 0.05). The post-TG cut-off point to best classify patients with respect to time to mortality was 1.47 mmol/L. A post-TG level of ≥ 1.47 mmol/L could independently predict a better OS (hazard ratio: 0.55, 95% confidence interval: 0.37–0.79). The associations were consistent across the subtypes of clinical parameters. Furthermore, the post-body mass index, post-subcutaneous adipose tissue area, post-visceral adipose tissue area, post-total adiposity tissue area, and post-total adipose density exhibited a strong positive association with post-TG levels. Conclusions: Post-TG levels were found to be a significant positive prognostic biomarker for body fat mass and OS in ESCC patients.